2015
DOI: 10.1007/s00216-015-8762-7
|View full text |Cite
|
Sign up to set email alerts
|

Determination of naturally occurring resveratrol analog trans-4,4′-dihydroxystilbene in rat plasma by liquid chromatography-tandem mass spectrometry: application to a pharmacokinetic study

Abstract: trans-4,4'-Dihydroxystilbene (DHS) is a naturally occurring resveratrol analog that displayed promising anti-cancer activities in pre-clinical studies. To further probe its therapeutic potential, a sensitive liquid chromatography-tandem mass spectrometry (LC-MS/MS) method was developed and validated for the measurement of DHS in rat plasma using electrospray ionization and multiple reaction monitoring in its negative ion mode. This analytical method demonstrated excellent linearity (R(2) > 0.99), selectivity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 22 publications
1
30
0
Order By: Relevance
“…Evaluate the effect of resveratrol on insulin resistance, glucose and lipid metabolism in non-alcoholic fatty liver disease (NAFLD) (Chen et al, 2015).…”
Section: Aim Treatment Resultsmentioning
confidence: 99%
“…Evaluate the effect of resveratrol on insulin resistance, glucose and lipid metabolism in non-alcoholic fatty liver disease (NAFLD) (Chen et al, 2015).…”
Section: Aim Treatment Resultsmentioning
confidence: 99%
“…In the recent years, considerable attention has been given to synthetic resveratrol derivatives, and numerous studies have reported that methoxylated, hydroxylated, and halogenated derivatives display more effective disease prevention characteristics than resveratrol . RV01 is the quinolyl‐substituted derivative of resveratrol.…”
Section: Discussionmentioning
confidence: 99%
“…The jugular veins of the rats were cannulated for blood sampling and i.v. dosing according to a well‐established protocol in our laboratory (Yeo et al, ; Chen et al, ).…”
Section: Methodsmentioning
confidence: 99%